Spotlight on Innovation : Making Things Happen with Scott Berkun - Berkun, Scott (O'Reilly Media, Inc., 2019)
Making Things Happen is among the most popular books on project management ever written, known for its direct, actionable, and humane advice on every aspect of leading teams and projects. For the book's 10th anniversary, author Scott Berkun presented a fast and fun summation of the book's core ideas and explained how you can apply them to the projects you're working on today. Recorded on July 10, 2019. See the original event page for resources for further learning. Find future live events to attend or watch recordings of other past events . O'Reilly Spotlight explores emerging business and technology topics and ideas through a series of one-hour interactive events. In live conversations, participants share their questions and ideas while hearing the experts' unique perspectives, insights, fears, and predictions for the future. In every edition of Spotlight on Innovation, you'll discover what successful companies have in common and how you can follow their lead with small practical steps to transform your organization and prepare for the Next Economy.